Muslim Palawan diversity and difference on the periphery of Philippine Islam - Eder, James F. (Philippine studies : historical and ethnographic viewpoints, 2010)
"Three significant forms of difference crosscut ethnic boundaries within the diverse population 75,000-100,000 Muslims who presently reside in southern Palawan. These include differences in length of residence and sense of place, in how Islam is known and practiced, and in acceptance of the Philippine state and associated institutions of pwer. The presence of these and other social differences between Muslims in Palawan makes both ethnic and religious labels of limited predictive value in regard to livelihood, class position, voting behavior, and other important dimensions of Muslim lives."l